Reiteration Theorems for Two-Parameter Limiting Real Interpolation Methods. (13th March 2016) - Ahmed, Irshaad; Ejaz, Tuba
Abstract : We introduce a limiting real interpolation method involving two scalar parameters. We derive Holmstedt-type estimates for this method that are applied to establish the reiteration theorems.